Gill denervation eliminates the barostatic reflex in a neotropical teleost, the tambaqui (Colossoma macropomum) - Armelin, Vinicius Araújo; Braga, Victor Hugo da Silva [UNESP]; Teixeira, Mariana Teodoro [UNESP]; Rantin, Francisco Tadeu; Florindo, Luiz Henrique [UNESP]; Kalinin, Ana Lúcia (Springer Nature, 2016)
The baroreflex is one of the most important regulators of cardiovascular homeostasis in vertebrates. It begins with the monitoring of arterial pressure by baroreceptors, which constantly provide the central nervous system with afferent information about the status of this variable. Any change in arterial pressure relative to its normal state triggers autonomic responses, which are characterized by an inversely proportional change in heart rate and systemic vascular resistance and which tend to restore pressure normality. Although the baroreceptors have been located in mammals and other terrestrial vertebrates, their location in fish is still not completely clear and remains quite controversial. Thus, the objective of this study was to locate the baroreceptors in a teleost, the Colossoma macropomum. To do so, the occurrence and efficiency of the baroreflex were both analyzed when this mechanism was induced by pressure imbalancements in intact fish (IN), first-gill-denervated fish (G1), and total-gill-denervated fish (G4). The pressure imbalances were initiated through the administration of the α1-adrenergic agonist phenylephrine (100 µg kg−1) and the α1-adrenergic antagonist prazosin (1 mg kg−1). The baroreflex responses were then analyzed using an electrocardiogram that allowed for the measurement of the heart rate, the relationship between pre- and post-pharmacological manipulation heart rates, the time required for maximum chronotropic baroreflex response, and total heart rate variability. The results revealed that the barostatic reflex was attenuated in the G1 group and nonexistent in G4 group, findings which indicate that baroreceptors are exclusively located in the gill arches of C. macropomum.
Keywords: Baroreceptor; Baroreflex; Gills; Tambaqui; Teleost